Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien BPJS Di UPT Puskesmas Sukarame Bandar Lampung - Fikri Aziz Darmawan; Puja Damaskha (Business and Enterpreneurship Journal (BEJ), 2023)
Health services are an important factor in improving the health and welfare of every human being throughout the world. Everyone has the right to obtain health services and the government is responsible for the availability of all forms of quality, safe, efficient and affordable health services for all levels of society. One of these efforts is to increase the availability and equity of basic health service facilities such as puskesmas in each region. This study aims to determine the effect of service quality on patient satisfaction using BPJS at the Sukarame Public Health Center in Bandar Lampung. In this study, the research method used is quantitative. The object of this study were patients using BPJS at the Sukarame Health Center. The data source used is primary data in the form of questionnaires, interviews, and observations. The population used was all patients using BPJS at the Sukarame Health Center. The research sample is 40 people. The analytical method used is simple linear regression analysis in the form of validity test, reliability test, t test. The results of the study show that service quality has a significant and significant effect on patient satisfaction using BPJS. This shows that each indicator of the variable has an influence on patient satisfaction. Service quality which consists of physical evidence, reliability, responsiveness, assurance and empathy will be very influential if implemented as well as possible will affect patient satisfaction. Keyword:services quality, patient satisfaction, public health center.